Study of Direct Torque Controlled 3-phase SCIM with Two and Three-level Inverters using ST-DTC and FR-DTC scheme - Tripathy, P. R.; Panigrahi, B. P. (Engineering, Technology & Applied Science Research, 2015)
DTC control strategy helps to obtain fast and smooth control in 3–phase induction motors. It does not depend upon the machine parameters and transformation of reference frames. Various control strategies on the Direct Torque Control (DTC) scheme have been carried out in the present study. The suggested scheme is meant for designing the low cost control circuit for DTC implementation on 3-phase SCIM. Three schemes with two types of inverters have been simulated in MATLAB (Simulink) environment and the THD ratio in each case has been studied along with Fast Fourier Transform (FFT) tools to compare the advantages.